Differential size variations between transcriptionally active and inactive telomeres of Trypanosoma brucei. - Pays, E (1983)
We have studied the genes coding for the variant-specific surface antigen (VSA) in a series of seven trypanosome clones derived from AnTat 1.1: 1.1 leads to 1.3 leads to 1.6 leads to 1.16 leads to 1.1C leads to 1.3B leads to 1.18 These genes are all telomeric (1-5), and their surrounding, although sometimes similar, differs in each case. The length between these antigen genes and the corresponding DNA end appears to increase at each antigenic switch, with however occasional sharp size reductions, often linked to the involvement of the telomere in gene expression. This increase is due to a constant "growth" of the telomeres, at a rate of about 28 bp per day in at least four cases and probably linked to chromosome duplication. The telomere harbouring the transcribed VSA gene is growing slightly faster (about 36 bp per day), and it is the only one whose size reduction is progressive, leading to a terminal length heterogeneity within a clone. As a result, the active VSA gene is found in a population of telomeres which, as the trypanosomes divide, becomes increasingly heterogeneous, with however a preferred discrete size class about 1.4 kb smaller. The fact that the "active" telomere is the only one in a chromatin conformation highly sensitive to DNAaseI (1-4, 6), suggests that chromatin structure influences the rate and extent of both size increase and shortening of telomeres.